Verse. Book one, The broken half - Beck, Sam (Freelance artist) (Beck, Sam (Freelance artist). Verse, 2021)
"Fife's plans to become an expert swordsmith are interrupted when he meets Neitya, an extraordinary girl unlike any he's ever met before ... primarily because of her horns and amnesia. Worryingly, she seems akin to the monstrous Vel who roam the countryside. but when Fife is attacked by the Vel, Neitya saves him by using a skill thought to be forever lost to everyone: Magic. Fife and Neitya decide to journey together, seeking the guidance they need to unravel the mystery of her origin."--Amazon